2009
DOI: 10.1097/mao.0b013e318194f84d
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Head-Mounted Vibrotactile Stimulation in Subjects With Bilateral Vestibular Loss

Abstract: Head-mounted vibrotactile stimulation produced significant improvement in postural stability in subjects with BVL undergoing SOT 5 and 6 testing with no effect on subjective visual vertical during DSVV testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 10 publications
7
31
0
2
Order By: Relevance
“…We did not find publications confirming that supplying BVA patients with any kind of biofeedback could allow them to remain standing for 20 s EC without assistance on tilting platforms. In contrast, a possibility to prolong the time-to-fall was previously reported in BVA patients tested with EC on a sway-referenced platform (Equitest, Neurocom) while supplying them with vibrotactile biofeedback [21]. Consistent with this data, the present study showed a significant prolongation of time-to-fall in the BVA subgroup.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We did not find publications confirming that supplying BVA patients with any kind of biofeedback could allow them to remain standing for 20 s EC without assistance on tilting platforms. In contrast, a possibility to prolong the time-to-fall was previously reported in BVA patients tested with EC on a sway-referenced platform (Equitest, Neurocom) while supplying them with vibrotactile biofeedback [21]. Consistent with this data, the present study showed a significant prolongation of time-to-fall in the BVA subgroup.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, analysis of the therapy effect in posturographic scores revealed similarities with those observed in patients wearing auditory [2,3,18,19,24,25], vibrotactile [6,21,25,26] or multi-modal [20,22] biofeedback devices providing a real-time postural signal. Our patients, however, were tested without feedback, 4 h after the last use of the BrainPort balance device.…”
Section: Discussionsupporting
confidence: 69%
“…Electrotactile [5,[17][18][19] and vibrotactile [20][21][22][23][24] feedback systems also seem to be suitable for vestibular substitution. Electrotactile feedback through the tongue is an elegant method to improve posture and balance, as it is a fully head-based system and because a learning-effect of several hours after removal of the prothesis has been shown [17].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, while testing sites for a tactile prosthesis to aid balance, Asseman, Bronstein, and Gresty (2005) report that stimulation of the forehead with 200-Hz vibration led to faster reaction times than when the same stimulus was presented to the sternum. Similarly, in a clinical study, Goebel et al (2009) successfully used a head-mounted array of four EAI C2 tactors (one placed on the middle of the forehead) to provide balance cues for patients with bilateral vestibular loss. Finally, Mortimer et al (2011) successfully presented spatiotemporal patterns across the forehead (using EAI C3 tactors) to assess perceptual changes resulting from sports-related concussion.…”
Section: General Equipment and Proceduresmentioning
confidence: 99%
“…[EAI], of Castleberry, FL) have been used in several clinical studies (e.g., Goebel et al, 2009;Mortimer et al, 2011), as well as basic tactile research (e.g., Cholewiak, Schwab, and Beede, 2003;Cholewiak, Brill, and Schwab, 2004). The stimulus was mechanical -no electricity passed from the tactor to the subject.…”
Section: Injury/discomfort From Vibrationmentioning
confidence: 99%